Influence of Mobile Phone Service and Corporate Image on Customer Satisfaction of Bank CIMB Niaga - Winda Sri Astuti Doloksaribu; Nora Anisa Br Sinulingga (Enrichment : Journal of Management, 2021)
Bank CIMB Niaga mobile phone account is the account banking service based of mobile phone first in Asia, banking transactions by using cell phone number without ATM card. it is limited research about the influence of the existence this service to the corporate image and customer satisfaction. The purpose of this study is to analyze the influence of the phone account service with customer satisfaction, the company's image and analyse the influence of the company’s image with customer satisfaction of Bank CIMB Niaga. This research was conducted in April-May2021 with 100 respondents who have used phone account at least one month. Respondents selected by convinience sampling in Sun Plaza Medan. Data obtained were processed by using the SEM analysis (Structural Equation Modelling) with SMART PLS. The results showed a positive influence mobile phone account services to the satisfaction of the customer and are not significant but contribute towards satisfaction through the company's image. The positive influence of corporate image satisfaction and significant.